Mapeamento e melhoria do fluxo de informações: aplicação do Lean Office no Centro de Engenharia de uma multinacional do setor alimentício - Araujo, Tatiana Mancilha de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Companie Managers have been looking for continuous improvement, reduced wastes and increased efficiency. The objective of this research is to improve the information flow of the processes of the engineering center of a multinational company of the food sector. It is function of the engineering center to integrate the administrative areas of the company and to give support to the productive units. furthermore, possible reductions of wastes and improvement of efficiency will have very positive impacts. After identifying the opportunities and possible benefits of the action-research resource, a systematic review of the literature was carried out that and it has contributed to the choice of Lean Office as the set of methodological tools to be employed. A total of twenty processes have been studied and improved, and despite of the difficulties founded, there were significant gains in time reduction

As direções das empresas têm buscado a melhoria contínua, a fim de obter redução de desperdícios e maior eficiência. O objetivo desta pesquisa-ação é melhorar os fluxos de informações dos processos do centro de engenharia de uma empresa multinacional do setor alimentício. É função do centro de engenharia integrar diferentes áreas da empresa e dar suporte às unidades produtivas; logo, possíveis reduções de desperdícios e ganhos de eficiência terão impactos positivos bastante amplos. Após a identificação das oportunidades e possíveis benefícios da pesquisa-ação, foi realizada uma revisão sistemática da literatura que contribuiu para a escolha do Lean Office como o conjunto de ferramentas metodológicas a serem empregadas. Um total de vinte processos foram mapeados e melhorados, e apesar das dificuldades encontradas, tiveram ganhos significativos na redução dos tempos
Mapping and improvement of the flow of information: application of the Lean Office in the Engineering Center of a multinational of the food sector
Keywords: Controle de processo; Controle de qualidade; Desperdício (Economia); Quality control